Perkembangan Material Barium Heksaferrit Doping Lantanum sebagai Penyerap Gelombang Elektromagnetik: Tinjauan Literatur - Intan Septia Sari Lubis; Miftahul Husnah (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of lanthanum-doped barium hexaferrite materials has attracted considerable attention in the field of functional materials, particularly as electromagnetic wave absorbers. This literature review aims to analyze advances in synthesis methods, structural characteristics, magnetic properties, and electromagnetic absorption performance of lanthanum-doped barium hexaferrite reported in various studies. Synthesis techniques such as sol–gel, coprecipitation, solid-state reaction, and hydrothermal methods are compared to evaluate their effects on crystallite size, morphology, and phase purity. Lanthanum doping is known to modify lattice parameters, reduce coercivity, and enhance complex permittivity and permeability, which play crucial roles in absorption mechanisms. Furthermore, variations in dopant concentration significantly influence reflection loss values and effective absorption bandwidth. The reviewed literature indicates that optimization of composition and synthesis routes can produce materials with high absorption capability, good stability, and strong potential for application in electromagnetic interference mitigation devices. This review is expected to serve as a conceptual reference for future development of lanthanum-doped barium hexaferrite–based electromagnetic wave absorbing materials. The comparative approach also highlights research challenges, industrial application opportunities, and future research directions relevant to the evolving demands of modern communication and defense technologies at both national and global levels.